1998
DOI: 10.1016/s1044-0305(98)00088-9
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of phosphopeptides in an ion trap mass spectrometer

Abstract: A systematic study of the fragmentation pattern of phosphopeptides in an electrospray (ESI) ion trap mass spectrometer is presented. We show that phosphotyrosine- and phosphothreonine-containing peptides show complicated fragmentation patterns. These phosphopeptides were observed to lose the phosphate moiety in the form of H3PO4 and/or HPO3, but were also detected with no loss of the phosphate group. The tendency to lose the phosphate moiety depends strongly on the charge state. Thus, the highest observed char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
316
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(335 citation statements)
references
References 18 publications
18
316
1
Order By: Relevance
“…The phosphate group was localized at serine 318 using the BioTool software (Bruker-Daltonics) consid- ering the dehydroalanine residue [22][23][24], formed by the loss of the H 3 PO 4 from the phosphoserine residue during gas phase dephosphorylation. By mutating serine 318 to alanine in IRS-1, this site was not phosphorylated by PKC-(unpublished observation), thus the results of the applied procedure were independently verified.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphate group was localized at serine 318 using the BioTool software (Bruker-Daltonics) consid- ering the dehydroalanine residue [22][23][24], formed by the loss of the H 3 PO 4 from the phosphoserine residue during gas phase dephosphorylation. By mutating serine 318 to alanine in IRS-1, this site was not phosphorylated by PKC-(unpublished observation), thus the results of the applied procedure were independently verified.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by others also noted a 98 Da loss from phosphotyrosine peptides [11,12,16], however, the reasons for this 98 Da loss is unclear. In order to explore fragmentation of the phosphate group from tyrosine, we employed the peptide Ac-RRLIEDAE(pY)AARGamide as a model.…”
Section: Ap Maldi/itmsmentioning
confidence: 86%
“…Several groups have investigated the gas phase dephosphorylation patterns of phosphorylated peptides and proteins [8 -21]. DeGnore and Qin [12] studied phosphopeptides by ESI/ ITMS. They reported that the loss of phosphate group is charge state dependent and that loss of phosphate from phosphoserine and phosphothreonine occurs via ␤-elimination.…”
mentioning
confidence: 99%
“…Precursor ion scanning [14,19], neutral loss scanning [23], and nozzle-skimmer dissociation [9] can determine the presence, absence, and location of peptide phosphorylation based on the unique mass losses associated with phosphorylated peptides. In MALDI-TOF mass spectrometry, postsource decay (PSD) of metastable ions formed in the source region via these characteristic pathways can also be used to determine sites of phosphorylation [17].…”
mentioning
confidence: 99%